Formulation and evaluation of microsphere of antiulcer drug using the Acacia nilotica gum: Acacia nilotica microsphere as antiulcer drug - Abrar, Anam; Yousuf, Shayasta; Dasan, M.K. (International Journal of Health Sciences, 2020)
Objective: This study was undertaken to evaluate the formulation of the microspheres for antiulcer drug using natural polymer Acacia nilotica gum. Materials and Methods: All parameters evaluated A. nilotica gum, aqueous solution of purified gum was used for chemical characterization, organoleptic character, flow properties, pH, particle size determination, solubility, viscosity, surface tension, infrared spectroscopy, etc. The microspheres of famotidine were prepared by ionotropic gelation technique using cross-linking solution of aluminum chloride, barium chloride, and calcium chloride. Results: Micrometric evaluation was performed of natural polymer microspheres. The micrometric parameters such as bulk density, bulkiness, compressibility index Hausner’s ratio, and angle of repose better flow and good packaging properties (bulk density F5±0.02) formulation F1 showed maximum tapped density 0.06±0.04. The concentration was changed of A. nilotica gum so formulation F5 given maximum percentage yield of microspheres. Particle size ranges 846.31–989.04 μm. Formulation F3 shows the smallest particle size and F5 shows the largest particle size. Swelling index for all the formulations was found in an excellent range from 114.2 to 144.4. Formulation F5 showed the highest swelling property. Highest drug content was found in formulation F1 ranged from 88.98% to 98.23%. In in vitro drug release, F1 showed maximum release of drug, whereas F6 showed minimum release of drug. Conclusions: Natural polymer A. nilotica gum was successfully used for the preparation of famotidine microparticulates. Formulation with A. nilotica gum was impacted to the particular size, surface morphology, swelling conduct, and in vitro drug release. Stability studies F1, F3, and F5 formulations showed no reduction in drug content and in percent release. In short, A. nilotica gum may be utilized during pharmaceutical dose frames by giving support to drug delivery system and avoiding side effects for the patients.